2015
DOI: 10.1177/1074248415583091
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Magnetic Resonance Spectroscopy as a Method for Evaluation of In Vivo Poly-l-Lactide Biodegradation Kinetics From Stent-Polymer Matrices

Abstract: The utilization of NMR method for BP absorption kinetics evaluation is a useful tool, which may be widely adopted to test other biodegradable implants. Further, it may substantially improve their safety and efficacy by facilitating programmed polymer and drugs elution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…1) [17]. The degradation of the polymer lasts approximately eight weeks [18]. The BiOSS LIM C ® stent consists of two main separate parts with different diameters: wider proximally, and distally smaller.…”
Section: Device Descriptionmentioning
confidence: 99%
“…1) [17]. The degradation of the polymer lasts approximately eight weeks [18]. The BiOSS LIM C ® stent consists of two main separate parts with different diameters: wider proximally, and distally smaller.…”
Section: Device Descriptionmentioning
confidence: 99%
“…The total mass of the polymer on a 3.0 × 15 mm stent does not exceed 360 μg. The experimental studies in the porcine in-stent restenosis model at 8 weeks has shown nearly full polymer biodegradation and 95% drug release of initial drug load [12]. The stent utilizes the L605 cobalt chromium alloy platform with strut thickness of 70 μm and closed cell design, which also served as bare metal control (BMS, Coflexus, Balton).…”
Section: Device Descriptionmentioning
confidence: 99%
“…The total mass of the polymer on a 3.0 × 15 mm stent does not exceed 360 μg. Experimental studies in the porcine in‐stent restenosis model at 8 weeks showed nearly full polymer biodegradation and 95% drug release of initial drug load . In the previously published study, BP‐SES demonstrated favorable performance in complex coronary lesions of 424 patients in daily clinical practice .…”
Section: Methodsmentioning
confidence: 73%
“…Experimental studies in the porcine in-stent restenosis model at 8 weeks showed nearly full polymer biodegradation and 95% drug release of initial drug load. 13 In the previously published study, BP-SES demonstrated favorable performance in complex coronary lesions of 424 patients in daily clinical practice. 14 BP-SES displayed high clinical device success (98.5%), and acute gain (1.67 AE 0.44 mm) together with low residual diameter stenosis (6.43 AE 4.16%).…”
Section: Stent System Descriptionmentioning
confidence: 90%